SARS-CoV-2 genome sequencing from COVID-19 in Ecuadorian patients: a whole country analysis - Márquez, Sully (medRxiv, 2021)
SARS-CoV-2, the etiological agent of COVID-19, was first described in Wuhan, China in December 2019 and has now spread globally. Ecuador was the second country in South America to confirm cases and Guayaquil was one of the first cities in the world to experience high mortality due to COVID-19. The aim of this study was to describe the lineages circulating throughout the country and to compare the mutations in local variants, to the reference strain. In this work we used the MinION platform (Oxford Nanopore Technologies) to sequence the whole SARS-CoV-2 genomes of 119 patients from all provinces of Ecuador, using the ARTIC network protocols. Our data from lineage assignment of the one hundred and nineteen whole genomes revealed twenty different lineages. All genomes presented differences in the S gene compared to the Wuhan reference strain, being the D614G amino acid replacement the most common change. The B.1.1.119 lineage was the most frequent and was found in several locations in the Coast and Andean region. Three sequences were assigned to the new B.1.1.7 lineage. Our work is an important contribution to the understanding of the epidemiology of SARS-CoV-2 in Ecuador and South America.